O cotidiano do ser-mãe-de-recém-nascido-prematuro diante da manutenção da lactação na UTI neonatal: possibilidades para a enfermagem - Tronco, Caroline Sissy (2012)
The research aim was to comprehend the everyday of mothers of premature new-born (PNB) admitted on neonatal intensive care unit (NICU) on maintaining lactation against the (im)possibility of breastfeeding. For this, it was developed a qualitative research with phenomenological approach. Data production happened on NICU of University Hospital of Santa Maria/RS, from December 2010 to April 2011. Seven phenomenological interviews were developed with the mothers of new born babies admitted in this unit and that were (un)able to breastfeed because of their baby s clinical conditions. Data analysis, based on theoretical methodological referential of Martin Heidegger, unveiled on vague and medium comprehension that, to the mothers of PNB in the NICU, the lactation maintenance against the (im)possibility of breastfeeding means having some kind of problem during pregnancy that made the baby to be born before the expected time. They want to know what the baby has and what s happening. They get worried about the situation and then calm down, but it s still difficult. They are afraid for the baby that was born before time, premature and small. The baby has to stay in the ICU and the mother has to go hope and leave the baby in the hospital. They wish their child was breastfeeding. It s difficult to take milk out and it hurts because it paves. To put their child on the breast make them feel more like mothers. Keeping the daily activities at home and having to go to the hospital is tiring. Time spent with the baby is good and it helps them. They pray for their baby to get better and gain weight so he/she can go home. They find support on the professionals and the family. On interpretative comprehension, mothers show themselves as being-a-PNB-mother against the double facticity of having a premature child and that he/she is admitted in the NICU. Trapped on the babble by repeating what led to the premature birth and about the importance of breast milk, curious about the baby's health. But the ambiguity remain at the thought that they understood the reason for premature delivery, when in fact not yet. It shows in the way of fear, in its three perspectives: terrified of preterm infants and small, horrified at the NICU and terrified by being discharged and having to leave the baby in the hospital. They keep themselves busy with milking and the routine of having to go and come home from the hospital, they show themselves as being-with the child when they put him/her to nursing, which enables to do the movement of occupation and pre-occupation. They are being-with the family and nursing staff, showing that they need support and that they keep themselves in decay, when they show themselves confirmed with the situation. The experience of being-a-PNB-mother points to the need to ally assistance to PNB to attention to the family, specially, to mothers. Besides bringing together the clinical and biological dimension, it s vital to the survival of the RNP, the subjective and social dimension of care to the triad mother/child/family.